2015
DOI: 10.1128/aac.01117-15
|View full text |Cite
|
Sign up to set email alerts
|

Sensititre MycoTB Plate Compared to Bactec MGIT 960 for First- and Second-Line Antituberculosis Drug Susceptibility Testing in Tanzania: a Call To Operationalize MICs

Abstract: c MIC testing for Mycobacterium tuberculosis is now commercially available. Drug susceptibility testing by the MycoTB MIC plate has not been directly compared to that by the Bactec MGIT 960. We describe a case of extensively drug-resistant tuberculosis (XDR-TB) in Tanzania where initial MIC testing may have prevented acquired resistance. From testing on archived isolates, the accuracy with the MycoTB plate was >90% for important first-and second-line drugs compared to that with the MGIT 960, and clinically use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 14 publications
1
38
1
Order By: Relevance
“…This means that analytical techniques in order to analyze amikacin or kanamycin in serum with high-throughput rates should be made available in all TB programs to deliver fast and accurate results. In addition, simple drug susceptibility testing in order to establish a precise MIC value should also be available (35). Both PK and PD analysis requires trained and experienced personnel with equipment.…”
Section: Discussionmentioning
confidence: 99%
“…This means that analytical techniques in order to analyze amikacin or kanamycin in serum with high-throughput rates should be made available in all TB programs to deliver fast and accurate results. In addition, simple drug susceptibility testing in order to establish a precise MIC value should also be available (35). Both PK and PD analysis requires trained and experienced personnel with equipment.…”
Section: Discussionmentioning
confidence: 99%
“…However, individualized treatment is based on true minimum inhibitory concentration (MIC) of drugs when testing the MTB isolate [17,51,52]. In addition to easy-to-implement MIC testing [109], a central reference laboratory is crucial for optimal treatment outcome in XDR-TB.…”
Section: Expert Commentarymentioning
confidence: 99%
“…The MIC of a drug was considered the lowest concentration able to inhibit the visible growth of a microorganism in a well. The resistance breakpoints were based on previously established concentrations [STR– 2.0, RMP– 1.0, rifabutin (RFB)– 0.5, INH– 0.2, EMB– 5.0, OFX– 2.0, MFX– 0.5, KAN–>5.0, AMK–>4.0, PAS– 2, ETH– 5, and D-cycloserine– 30 μg/ml] [17]. A correlation analysis of the MICs for pairs of drugs was performed using the Statistica software version 10 (Dell Software, Tulsa, OK, USA).…”
Section: Methodsmentioning
confidence: 99%
“…MycoTB is an inexpensive method to simultaneously identify the minimal inhibitory concentrations (MICs) of twelve first- and second-line drugs. Previous studies have demonstrated the method’s good reliability and reproducibility for most drugs compared with the agar proportion method [8, 11, 16] and the MGIT method [8, 17]. In this study, we compared these two phenotypic methods using clinical strains isolated in the Moscow region of Russia.…”
Section: Introductionmentioning
confidence: 99%